Environmentally Friendly Zeolites Synthesis and Source Materials - Chaves Lima, Rafael; Bieseki, Lindiane; Vinaches Melguizo, Paloma; Castellã Pergher, Sibele Berenice (Engineering Materials, 2019)
This book details zeolites, their structures and the parameters that influence their synthesis, providing a new and actual perspective of this field. Following this, the authors show different processes used to synthesize zeolites using residues, natural materials, and other eco-friendly materials such as raw powder glass, clays, aluminum cans, diatomites, rice ashes or coal ashes. Finally, this book gives the reader a wide range of different synthesis methods that they can be applied to several industrial processes.